Novelar la historia del Caribe colombiano, su mito fundacional y el mestizaje entre los sexos. Juan José Nieto Gil, 1844 - Goldwaser Yankelevich, Nathalie R. (CIICLA, Universidad de Costa Rica, 2020)
Based on the study of the novel Ingermina or the daughter of Calamar (1844) by the New Granadine author Juan José Nieto Gil (1805-1863), this essay aims to glimpse an aspect of the Colombian Caribbean: the integration of native peoples with European culture as a necessary fact in the process of building a nation. It is hypothesized that the author, observing the need for a civic nation, tried to reconstruct a kind of "myth of origin" typical of the need to create a collective "us", under a liberal and republican tinge. A clear example is given in the descriptions of the different figures of women that occupy a large part of the story. Cartagena was one of the last major cities of New Granada to be liberated from the Spanish yoke (November 1811). To demonstrate the imbrication of the times of political construction, the text-context methodology becomes a useful analysis tool. This allows this literature to be considered as historical evidence of an immemorial space-time.